STUDI PERBANDINGAN HASIL BELAJAR MAHASISWA YANG BERASAL DARI SMK DENGAN SMA PADA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN JURUSAN TEKNIK SIPIL FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - 75-82 . Prayudi Ariesky (Universitas Negeri Padang, 2013)
The title of this research is the Comparative Result of Learning of Students who graduated from senior high school (SMA) and senior high school of engineering (SMK) at Engineering Educational Program of Enggineering Faculty of Padang State University (UNP), the aims of this research are to desribe and compare the comulative grade of students from first semester to the third semester. The number of data for comparation are 55 students graduated from senior haigh school of engineering and 39 students graduated from senior high school. The analyzed data are collected from BAAK (Academic Affairs Administrative Bureau). The data was analyzed by using the two test mean difference method (t-test). The result shows that there is no difference between graduated from senior high school of engineering and senior high school at the first and the second semester with the value of ratio > 1.663 and a difference in semester III with the value of ratio <1.663 and 0.05 confidence level. Based on the analysis, no difference for 1st and 2nd semester because the subjects are general subjects.